A comparison of Male and Female Medical Student’s Motivation towards Career Choice - Hina Sattar, Zubaida Zain, Abdul Malik Sheikh, Aniqua Saleem, Muhammad Arshad, Lubna Meraj (Journal of Rawalpindi Medical College, 2021)
Objective: To compare motivation to become a doctor in both genders Study Design: Observational cross-sectional study Place and Duration of Study: Rawalpindi Medical University in March 2019. Materials and Methods: First and second-year M.B.B.S students were included in the study. Age, year of study, and gender were recorded. The questionnaire included 18 questions assessing six motivational dimensions: status and security; nature of the occupation; career opportunities; patient care and working with people; use of personal skills; and interest in science. Responses were recorded as ‘agree’ or ‘disagree’ for each question and results were analyzed using SPSS v19. Results: Out of 350 medical students, 247 (70.6%) were female and 103 (29.4%) were male. Most frequent motivational factors for females were “Opportunity to care for/ help people” (n=240; 97.1%) followed by “responsible job” (n=220; 89%) and “use of mental skills” (n=217; 87.8%). Male students were motivated mostly by “use of mental skills” (n=90; 87.3%) followed by “provides secure career” (n=87; 84.4%) and “challenging field” (n=83; 80.5%). In our study, (n=61; 25%) of females responded in agreement that boosts in marriage perspective was an underlying motivational factor for their choice of studying medicine while (n=41; 40%) males agreed to it. There was a significant difference between both genders with a p-value of 0.005. Conclusions: We infer that female medical students have more humanitarian grounds for choosing the medical profession and are more motivated than their male counterparts.